Epithelial ovarian cancer in the young in Siriraj Hospital - Phakawan Thornprateepchot; Atthapon Jaishuen; Suwanit Therasakvichya; Wiboolphan Thitadilok; Suthipol Udompunturak (The Royal Thai College of Obstetricians and Gynaecologists, 2009)
Objective: To access incidence, risk factors, 5-year progression free survival and overall survival in young patients with epithelial ovarian cancer (EOC) in Siriraj Hospital. Methods: Medical records of patients equal or younger than 40 year of age treated with EOC in Siriraj Hospital from January 1998 to December 2007 were reviewed for clinical characteristics, treatments, and outcomes. Survival curves were generated using Kaplan-Meier method. Cox regression analysis to determine multivariate factor for recurrence and survival was performed. Results: Incidence of patients equal or younger than 40 year old with EOC in Siriraj Hospital was 5.8 % of all EOC. Mean age was 33.4±5.4 years. Sixty five percents of patients had abnormal pretreatment CA-125 level. Majority of the patients were in stage I of EOC. Sixty five percents of patients underwent optimal surgery. Adjuvant chemotherapy was applied in 83.7%. Twenty two patients were dead with a median time to death of 3 months. Five-year progression survival was 84.8% and 5-year overall survival was 76% with the median follow up time of 20.5 months. Abnormal pretreatment CA-125 level and suboptimal surgery were the only two independent prognostic factors for survival. Conclusions: The incidence of EOC in the patients equal or younger than 40 year of age is 5.8% of all EOC. The 5-year overall survival rate was 76%. From multivariate analysis, the independent prognostic factors for overall survival were abnormal pretreatment CA-125 level and suboptimal surgery with the hazard ratio of 6.69 (P<0.001) and 2.79 (P=0.033).